2006
DOI: 10.1177/102425890601200306
|View full text |Cite
|
Sign up to set email alerts
|

The governability of collective bargaining. The case of Spain

Abstract: ABSTRACT:The aim of this article is to analyse the concept of governability of collective bargaining proposed by Traxler, Blaschke and Kittel (2001) and to demonstrate its explanatory capacity and limitations in the Spanish case. Governability is today an important subject that should be taken into account in the reform of industrial relations systems and in the debate between centralisation and decentralisation of collective bargaining in Europe. Our main hypothesis is drawn up in line with the institutionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Alternatively, the articulation between levels under multi-employer bargaining may not be well-specified. The more isolated is decentralized collective pay determination from a wider sectoral or cross-sectoral frame work, the more contingent local pay policies and outcomes become on the power and resources of representatives and the greater the space for unilateral management initiatives (Nonell et al, 2006;Visser, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the articulation between levels under multi-employer bargaining may not be well-specified. The more isolated is decentralized collective pay determination from a wider sectoral or cross-sectoral frame work, the more contingent local pay policies and outcomes become on the power and resources of representatives and the greater the space for unilateral management initiatives (Nonell et al, 2006;Visser, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the negotiated change between trade unions and employers' organizations towards new forms of governance has been to some extent cosmetic, as inter-associational coordination remains fragile and 'sustained' by the threat of unilateral government intervention (as in 1994 and 2001) and not by shared objectives and consensus. As pointed out by Nonell et al (2006), the law is still a key factor contributing to the governability of the Spanish industrial relations system. This leads us to the second question posed at the beginning of the paper, i.e.…”
Section: South European Society and Politics 473mentioning
confidence: 98%
“…Notwithstanding the social partners' discontent with the characteristics of collective bargaining, attempts at renegotiation and reform failed in the 1980s for two main reasons. First, a highly juridified industrial relations system, though providing some governability (Nonell et al 2006), had nonetheless undermined the role of autonomous bargaining as a source of innovative regulation from within the system. Relations between unions and employers were characterized by some kind of regulated antagonism, which not only perpetuated conflict, but curtailed actors' abilities to find negotiated solutions (Rigby & Marco 2001).…”
Section: The Genesis Of Industrial Relations In Spain: the Statist Lementioning
confidence: 99%
“…Nonell, Alós-Moner, Artiles and Molins (2006) analysed vertical and horizontal coordination before the economic crisis of the Great Recession and concluded that governance in the industrial relations system rests on specific legal and cultural elements. However, wage bargaining mechanisms have been conditioned by competitive social concertation (Fernández, Ibañez & Martínez, 2016), according to which wage moderation was a necessary condition for achieving macroeconomic stability.…”
Section: Institutional Developmentsmentioning
confidence: 99%